182k views
12 votes

=x^(2) -6x+5

=x^(2) -6x+5-example-1

2 Answers

8 votes

a) y-intercept = 5

b)
(x-1)(x-5)

step 1: find factors of 1st and last terms

step 2: multiply the factors "rainbow" style (like in the picture) and add the products to make sure they equal the middle term


x^(2) -6x+5\\1,1
-1,-5


(-1)+(-5)=-6\\=(x-1)(x-5)

c)
x=1,5


(x-1)(x-5)\\x-1=0
x-5=0


x=1
x=5

d) AoS=
x=3

e)
vertex=(3,-4)


(h,k)\\h=-(b)/(2a) \\h=-((-6))/(2(1)) \\h=-(-3)\\h=3\\k=f(3)=(3)^2-6(3)+5\\k=9-18+5\\k=-4

=x^(2) -6x+5-example-1
User Sagneta
by
5.9k points
8 votes

x= -1

your solve X that is it

=x^(2) -6x+5-example-1
User Zooba
by
5.9k points